The Higher Order Thinking Skills of Mathematics Education Students at State Islamic Higher Education in Central Sumatera - Rivdya Eliza; Nita Putri Utami; Selvi Warahma (Edumatika : Jurnal Riset Pendidikan Matematika, 2022)
The Higher Order Thinking Skills (HOTS) are some of the various competencies that prospective mathematics teachers must have in facing the challenges of the 21st century. This study aims to map the high-order thinking skills of Mathematics Education students at State Islamic Religious Higher Education (PTKIN) in Central Sumatera. This research is a descriptive quantitative study involving 310 Mathematics Education students at State Islamic University of (UIN) Imam Bonjol Padang, State Islamic Institute of (IAIN) Batusangkar, IAIN Bukittinggi, UIN Sultan Syarif Kasim Riau, UIN Sultan Thaha Saifuddin Jambi, and IAIN Kerinci. Data was collected through the Higher Order Thinking Skills (HOTS) test. The results showed that the average of high-order thinking skills of Tadris Mathematics students at PTKIN in Central Sumatera was relatively low. The results of this study reflect the readiness of prospective mathematics teacher students at PTKIN in welcoming the 21st century. The researchers recommend selecting appropriate learning methods to improve students' higher-order thinking skills and increase HOTS content in various courses.